2020
DOI: 10.3390/diagnostics10121104
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Short-Term and Ultra-Short Term Heart Rate, Respiratory Rate, and Time-Domain Heart Rate Variability Parameters during Sympathetic Nervous System Activity Stimulation in Elite Modern Pentathlonists—A Pilot Study

Abstract: Monitoring of markers reflecting cardiac autonomic activity before and during stressful situations may be useful for identifying the physiological state of an athlete and may have medical or performance implications. The study aimed to determine group and individual changes in short-term (5 min) and ultra-short-term (1 min) heart rate (HR), respiratory rate (RespRate), and time-domain heart rate variability (HRV) parameters during sympathetic nervous system activity (SNSa) stimulation among professional endura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Study protocol with details is presented in Figure 1 . Details of the study population (participants), study protocol, ECG acquisition, respiratory rate recordings, and SNSa stimulation have been presented elsewhere ( Gąsior et al, 2020 ; Hoffmann et al, 2020 ). The study was approved by the University Ethical Committee (SKE 01-01/2017, 7 March 2017, Warsaw, Poland) and followed the rules and principles of the Helsinki Declaration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study protocol with details is presented in Figure 1 . Details of the study population (participants), study protocol, ECG acquisition, respiratory rate recordings, and SNSa stimulation have been presented elsewhere ( Gąsior et al, 2020 ; Hoffmann et al, 2020 ). The study was approved by the University Ethical Committee (SKE 01-01/2017, 7 March 2017, Warsaw, Poland) and followed the rules and principles of the Helsinki Declaration.…”
Section: Methodsmentioning
confidence: 99%
“…HRV analysis has been mostly performed on the basis of group changes in endurance athletes ( Baumert et al, 2006 ; Schmitt et al, 2018 ; Deus et al, 2019 ), which is ineffective in detecting individual athletes’ responses ( Muñoz-López and Naranjo-Orellana, 2020 ). Greater attention to individual analysis seems to be necessary when assessing physiological responses to a specific training or interventions in athletes ( Gąsior et al, 2020 ; Hoffmann et al, 2020 ). Cardiac autonomic modulation is linked to spontaneous respiration ( Eckberg and Eckberg, 1982 ; Eckberg et al, 1985 ; Eckberg, 2003 ; Narkiewicz et al, 2006 ; Bari et al, 2016 ), hence, HRV (mostly frequency-domain) parameters are affected by respiratory depth and frequency ( Hirsch and Bishop, 1981 ; Brown et al, 1993 ; De Souza et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rapid, reliable, and sensitive HRV metrics permit noninvasive evaluations of autonomic homeostasis (parasympathetic and sympathetic activity), with a higher HRV value reflecting parasympathetic dominance and physical activity readiness [ 9 , 17 ]. While several HRV-guided training strategies have been proposed [ 18 ], recent work using individual HRV values to determine a compensation level to manage the training process has proven to be particularly effective [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…She assessed several morphological and biochemical markers, of which percentage of monocytes, the concentration of sodium, and total calcium were found as predictors of peak oxygen uptake in the regression model [ 9 ]. In a series of two articles, Gąsior & Hoffmann et al focus on the analysis of heart rate (HR), respiratory rate, and heart rate variability (HRV) parameters as potential markers of fatigue and overtraining [ 10 , 11 ]. For that purpose, they studied a group of 12 elite modern pentathlonists and described baseline responses of the studied parameters to sympathetic nervous system activity stimulation, suggesting that the analysis should be individualized [ 10 ].…”
mentioning
confidence: 99%
“…For that purpose, they studied a group of 12 elite modern pentathlonists and described baseline responses of the studied parameters to sympathetic nervous system activity stimulation, suggesting that the analysis should be individualized [ 10 ]. They also found that HRV should be interpreted concerning concomitant differences in HR and respiratory rate and technique of registration [ 11 ].…”
mentioning
confidence: 99%